Crystal structures of two monomeric triosephosphate isomerase variants identified via a directed‐evolution protocol selecting for l‐arabinose isomerase activity. Issue 6 (1st June 2016) - Krause, Mirja; Kiema, Tiila-Riikka; Neubauer, Peter; Wierenga, Rik K.
Abstract : Crystal structures are described of two monomeric triosephosphate isomerase (TIM) variants (Ma18, with four point mutations, and Ma21, with one point mutation) that were identified via a directed‐evolution protocol (starting from A‐TIM) and that have enhanced in vivo l ‐arabinose isomerase activity. The two structures show that the point mutations cause only minor structural changes, and for Ma21 the small structural changes near Asn11 of loop 1 rationalize its different binding properties. Abstract : The crystal structures are described of two variants of A‐TIM: Ma18 (2.7 Å resolution) and Ma21 (1.55 Å resolution). A‐TIM is a monomeric loop‐deletion variant of triosephosphate isomerase (TIM) which has lost the TIM catalytic properties. Ma18 and Ma21 were identified after extensive directed‐evolution selection experiments using an Escherichia coli l ‐arabinose isomerase knockout strain expressing a randomly mutated A‐TIM gene. These variants facilitate better growth of the Escherichia coli selection strain in medium supplemented with 40 m M l ‐arabinose. Ma18 and Ma21 differ from A‐TIM by four and one point mutations, respectively. Ma18 and Ma21 are more stable proteins than A‐TIM, as judged from CD melting experiments. Like A‐TIM, both proteins are monomeric in solution. In the Ma18 crystal structure loop 6 is open and in the Ma21 crystal structure loop 6 is closed, being stabilized by a bound glycolate molecule. The crystal structures show only small differences in the active site compared with A‐TIM. In the case of Ma21 it is observed that the point mutation (Q65L) contributes to small structural rearrangements near Asn11 of loop 1, which correlate with different ligand‐binding properties such as a loss of citrate binding in the active site. The Ma21 structure also shows that its Leu65 side chain is involved in van der Waals interactions with neighbouring hydrophobic side‐chain moieties, correlating with its increased stability. The experimental data suggest that the increased stability and solubility properties of Ma21 and Ma18 compared with A‐TIM cause better growth of the selection strain when coexpressing Ma21 and Ma18 instead of A‐TIM.